The diplomatic presidency : American foreign policy from FDR to George H.W. Bush - Chavez, Tizoc Victor Hutchinson (University Press of Kansas, 2022)
"The Diplomatic Presidency examines how modern US presidents-through correspondence, telephone calls, and face-to-face meetings-increasingly interacted with other world leaders. Historians and political scientists have overlooked the central role that leader-to-leader diplomacy came to play in the conduct of US foreign affairs and what it meant for presidential leadership at home and abroad. To address this oversight, the study spans the history of the presidency from Franklin Roosevelt to Bill Clinton. FDR's presidency established the pattern for future presidents by greatly expanding the scope and magnitude of presidential personal diplomacy. Whereas previous scholarship has tended to focus on the personalities or preferences of individual presidents, Tizoc Chavez argues that post-WWII presidents acted quite similarly in their use of personal diplomacy and did so for similar reasons. He reframes the historiographical conversation by shifting from a narrow focus on presidential uniqueness to a wider lens that recognizes similarities and connections across the presidency, which explains how an unwritten law barring the use of personal diplomacy transformed into an expectation of its use. Chavez identifies four major factors in this rise of personal diplomacy: a changing international environment, developments internal to the presidency, the desire of foreign leaders to interact directly with the US president, and domestic political incentives. The result has been that what was once effectively prohibited has become normal and expected"--